Solidarity Economy Reintegration Entities in Warmia and Mazury - Łojko, Majka (Olsztyn Economic Journal, 2021)
The aim of the paper is to present solidarity economy reintegration entities and to analyse the actions they undertake for labour market reintegration and social inclusion of people at risk of social exclusion and for social and vocational rehabilitation of the disabled in the Warmia and Mazury region. The paper provides a review of the literature on the subject, based on an analysis of data from public statistics published by Statistics Poland, current studies of the Regional Centre of Social Policy in Olsztyn and scientific studies dedicated to the field of the social and solidarity economy. The analysis has revealed that all solidarity economy entities operating in the region are focused on taking comprehensive measures aimed at counteracting social exclusion and promoting social and vocational reintegration of people who, for various reasons, are not able to perform their social and professional roles independently and effectively.